Strengthening of ground forces as an indicator of Poland’s foreign policy priorities - Philip O. Trunov (Научно-аналитический вестник Института Европы РАН)
Poland seeks to play an increased role in the confrontation between the West and Russia, in the distribution of NATO multilateral resources. Warsaw has chosen a noticeable increase of its land forces as an important attribute of its attractiveness to Western partners. The article tried to analyze the evolution of the structure and location of Polish land forces, basing on it to determine some Warsaw’s foreign policy’ priorities. Methodologically, the author relied on the provisions of the theory of armed forces’ building. If the «old» NATO member states have faced with the problem of increasing the military personnel in 2014–2023, then the «new» ones, especially Poland, in general successfully have grown their armed forces. The article compares the models of armed forces of Poland and Germany as the state which tried to make an increased contribution to NATO military groups. The difference between the rapid creation of land brigades and divisions in Polish army and the slow speed for German one is presented. This has become an advantage for Warsaw in its informal leadership dispute with Berlin. The illustrative is the location of rather powerful Polish land forces group in its western voivodeships, adjacent to Germany. Only since the end of 2010s Warsaw started to reinforce its group near Russian Kaliningrad region. Since the beginning of the 2020s Poland has begun the creation of powerful forces near Belarus, which reflected a noticeable change in its perception. The article explores of Poland for the operational use of its ground forces in Western Ukraine.